Dr. Lee Chia Kuang invents new software Dematel Digraph - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2021)
A lecturer from the Faculty of Industrial Management (FPI), Universiti Malaysia Pahang (UMP), Dr. Lee Chia Kuang, 35, created a new software called Dematel Digraph.